2016
DOI: 10.1016/j.jssr.2015.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Parents', Students', and Teachers' Beliefs about Teaching Heritage Histories in Public School History Classrooms

Abstract: This qualitative study examines the expectations and beliefs parents, students, and teachers have about the teaching of heritage histories in public high schools. Students from three heritage groups, as well as their parents and teachers, were interviewed to shed light on this complex, often silent, relationship. This study is grounded in literature about the purposes of history education, historical distance, and collective memory/heritage, which give shape to and help to explicate some of the more complex is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
1
3
0
1
Order By: Relevance
“…We contend that while students of color ideally should have access to culturally affirming knowledge inside social studies classrooms, this experience demonstrates why that kind of knowledge can only be engaged effectively within learning spaces that challenge the norms of conventional social studies education. While we agree with researchers who assert that talking about race and racism in U.S. social studies classrooms is foundational in dismantling the everyday White supremacy present in schools (Blum, 2012;Chikkatur, 2013;Ellsworth, 1989;Epstein, 2000;Howard, 2004;King, 2014;Levy, 2016;Martell, 2013Martell, , 2017Woodson, 2016), this study demonstrates how the continued presence of racialized power relations in our schools can make it difficult to do so. We start by describing the research methodology and theoretical framework and by situating the classroom context and the study.…”
supporting
confidence: 83%
“…We contend that while students of color ideally should have access to culturally affirming knowledge inside social studies classrooms, this experience demonstrates why that kind of knowledge can only be engaged effectively within learning spaces that challenge the norms of conventional social studies education. While we agree with researchers who assert that talking about race and racism in U.S. social studies classrooms is foundational in dismantling the everyday White supremacy present in schools (Blum, 2012;Chikkatur, 2013;Ellsworth, 1989;Epstein, 2000;Howard, 2004;King, 2014;Levy, 2016;Martell, 2013Martell, , 2017Woodson, 2016), this study demonstrates how the continued presence of racialized power relations in our schools can make it difficult to do so. We start by describing the research methodology and theoretical framework and by situating the classroom context and the study.…”
supporting
confidence: 83%
“…Bu araştırmalar, ağırlıklı olarak öğrenciler, öğretmenler ve aday öğretmenlerle yürütülmüştür. İlk gruptaki araştırmalarda, daha çok öğrencilerin kültürel mirasla ilgili alanlar hakkındaki bilgi (Akkaya, 2017), deneyim (Aslan ve Çulha, 2008), görüş (Gürdoğan-Bayır ve Çengelci-Köse, 2019;Gürel ve Çetin, 2019;Karakuş, Çepni ve Kılcan, 2011) algı (Levy, 2016;Tuncel ve Altuntaş, 2020), tutum (Arıkan ve Doğan, 2013;Dönmez ve Yeşilbursa, 2014;Ismaeel ve Al-Abdullatif, 2016) ve farkındalık (Sağ ve Ünal, 2019;Uztemur, Dinc ve Acun, 2019) durumlarının değerlendirildiğini söylemek mümkündür. İkinci grupta, öğretmenlerle yapılan çalışmalarda (Adukaite, van Zyl, Er ve Cantoni, 2017;Avcı ve Memişoğlu, 2016;Giménez, Ruiz ve Listán, 2008;Kafol, Dena ve Znidarsic, 2015;Lee ve Bang, 2011;Levy, 2016;Özlek, 2019;Pérez, López ve Listán, 2010), çeşitli branşlardaki öğretmenlerin kültürel miras konuları ve öğretimi hakkındaki görüşlerine başvurulmuştur.…”
Section: İlgili Araştırmalarunclassified
“…These studies have been predominantly carried out with students, teachers, and teacher candidates. It can be seen that the students' knowledge, viewpoint, perception, attitude, and awareness of the areas relevant to cultural heritage were assessed in the studies of the first group (Akkaya, 2017;Arıkan and Doğan, 2013;Aslan ve Çulha, 2008;Dönmez and Yeşilbursa, 2014;Gürdoğan-Bayır and Çengelci-Köse, 2019;Gürel and Çetin, 2019;Ismaeel and Al-Abdullatif, 2016;Karakuş, Çepni and Kılcan, 2011;Levy, 2016;Sağ and Ünal, 2019;Tuncel and Altuntaş, 2020;Uztemur, Dinc and Acun, 2019). In second group studies have focused on the insights of teachers in different branches on cultural heritage issues and its teaching (Adukaite, van Zyl, Er and Cantoni, 2017;Avcı and Memişoğlu, 2016;Giménez, Ruiz and Listán, 2008;Kafol, Dena and Znidarsic, 2015;Lee and Bang, 2011;Levy, 2016;Özlek, 2019;Pérez, López and Listán, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Social Studies scholarship has identified that students of different racial, ethnic, and cultural backgrounds and identities have divergent understandings of history (An, 2009; Barton, 2001; Epstein, 1998; Levy, 2016; Peck, 2010). Additionally, scholars have studied how students of color distrust social studies teachers and the curriculum, even going so far as to call the official history narratives lies (Busey & Russell, 2016; Santiago, 2017; Woodson, 2016, 2018).…”
mentioning
confidence: 99%